Supplements of an aqueous combination of Justicia adhatoda and Ocimum tenuiflorum boost antioxidative effects and impede hyperlipidemia - Iqbal Chowdhury, Ifrahim (Animal Model Exp Med, 2020)
BACKGROUND: Justicia adhatoda and Ocimum tenuiflorum, locally known as bashok and tulsi, are two ethnomedicinally important herbs that have been using as dietary supplements for several therapeutic applications. This study evaluated the combined effect of both the herbs as an antioxidative and antihyperlipidemic agent. METHODS: Antihyperlipidemic effect was assessed in a high‐fat diet‐induced hyperlipidemic model in Wistar albino rats. The rats were treated orally with extracts of bashok (J adhatoda, 200 mg/kg bw), tulshi (O tenuiflorum, 200 mg/kg bw), and a combination of bashok and tulshi (50:50), as well as with a reference drug, atorvastatin (10 mg/kg/day), with or without high‐fat diet for 14 days. The antioxidative effect was studied using established in vitro models. The studies were supported by experimentally testing the effects of the extracts on membrane stabilization and inhibition of protein denaturation. RESULTS: The results showed that the serum lipid profile was significantly decreased in the different treatment groups, with bashok having the greatest effect. Body weights, total serum protein, LDH, and relative liver and adipose tissue weights were markedly restored towards baseline values, the lowest atherogenic index being achieved with the combined extract. The combination treatment significantly enhanced total phenolic content and antioxidative capacity and greatly potentiated membrane stabilization, but inhibition of protein denaturation was not significantly affected. CONCLUSION: The data demonstrate that a combination of Justicia adhatoda and Ocimum tenuiflorum could be developed as a food supplement with antioxidative and antihyperlipidemic benefits.